2x(0)-3y=6

Simple and best practice solution for 2x(0)-3y=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x(0)-3y=6 equation:


Simplifying
2x(0) + -3y = 6

Reorder the terms for easier multiplication:
2 * 0x + -3y = 6

Multiply 2 * 0
0x + -3y = 6

Anything times zero is zero.
0x + -3y = 6
Remove the zero:
-3y = 6

Solving
-3y = 6

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Divide each side by '-3'.
y = -2

Simplifying
y = -2

See similar equations:

| 8-(2a+7)=a+40 | | X^3-x^2+x=1 | | 7.26x+7.26=14.52 | | X+4=-5x-7 | | 6x+8=8-x | | 7(Y-1)=-42 | | 3(4-a)=2(a+6) | | -13(n+20)=(-11n+38) | | 0=9x^2-2kx+3k | | 9-x*1/2=13 | | 24=2/3V | | 5/12/360 | | -2x-3y=-30 | | 2.25+3.50x=44.25 | | 360/6x | | 2(10x-5)=4(5x+2) | | 14p+20q+p-7q-3p= | | 44.25=2.25+3.50x | | 6/7=3V | | 2-3(y-5)=3+(y+1) | | 4z+6= | | 2t-4s-2t+4s= | | (4b+7)-(6b-3)= | | 12=n-10 | | -x-5y=-54 | | 6x-12=3610x | | f(x)=-0.04x^2+0.8x | | 5(3e+2e-g)= | | 4s+5+5s-5= | | 3m-500=356 | | 2-4x=-7-1x | | 3a+ap=4p |

Equations solver categories